The antimicrobial role of emulsifying salts against E.coli O157:H7 contaminated local markets soft cheese of Baquba city - Al-Shedidi, Ahmed M.S. (The Iraqi Journal of Veterinary Medicine, 2017)
The aim of this study was to investigate the degree of contamination of locally produced soft cheese samples by Escherichia coli O157:H7 and to determine the ideal emulsifying salts and their appropriate ratios for emulsification of soft cheese and their impacts on microbial load of that influence public health. Samples collected randomly from five popular parties markets affiliated to the city of Baquba 60 samples of the local soft cheese produced by farmers at a rate of 30 samples for each of the summer season, from the beginning of July to the end of August, while the other thirty sample of winter season were collected from the beginning of December to the end of January to study their bacterial load of coli form and Escherichia coli especially E. coli O157:H7. The result showed total bacterial count characterized by high significance (P<0.01) in the local cheese samples of summer and winter season also. The results proved the bactericidal and bacteriostatic effect of emulsifying salts on microbial activity was confirmed when the total bacterial count was significantly (P<0.01) reduced in soft cheese with (2.5%) of emulsifying salts added. Were no growth of E. coli and E. coli O157:H7 after adding (2%) of emulsifying salts to nutrient broth and the results confirmed that the best mixing of the components of emulsifying salts that is made up of (90% Sodium tripolyphosphate + 10% Trisodium citrate).